Future Production Prediction for Ghani Oil Field by using Prosper Software with Decline Curve Analysis - Hayat Alhaj; Adel Traki (AlQalam Journal of Medical and Applied Sciences, 2026)
Nodal Analysis, defined as a systems approach to the optimization of oil and gas wells, is used to evaluate a complete producing system thoroughly. Every component in a producing well or all wells in a producing system can be optimized to achieve the objective flow rate most economically. In our study, two wells from the Ghani oil field have been used as a case study. Three production tests and a flowing pressure survey were collected and analysed using PROSPER Software to estimate the well productivity index at different times, as well as to calculate and plot the pressure gradient and compare the results obtained by different methods with the actual one. Consequently, to find the best method that gives us the least value of error comparing with actual one used to construct IPR-VLP performance (Nodal Analysis). The measured vertical flow pressures, for most wells, matched very well with the Fancher-Brown multiphase vertical correlation pressure. This behaviour is obtained because the wells are producing under natural flow. The sensitivity analysis has been performed to predict the future reservoir performance at different reservoir pressures, water cut, and Gas Oil Ratio (GOR). In the selected wells, the total oil reserves, remaining reserves and remaining productive life were estimated using Decline Curve Analysis (DCA), furthermore and at time in future, we could predict the future oil flow rate, reservoir pressure and bottom hole flowing pressure by linking the Decline Curve Analysis with the Nodal Analysis, finally, the prediction results revealed that the wells can continue producing for only a few more years.